Epictia albipuncta burmeister, 1861 (Serpentes : Leptotyphlopidae) first record for the Formosa province, Argentina - Ruiz García, José Augusto (2020)
Fil: Ruiz García, José Augusto. Universidad Nacional del Nordeste. Facultad de Ciencias Exactas, Naturales y Agrimensura; Argentina.